HYPOLIPIDEMICEFFECT OF AVOCADO (PERSEA AMERICANA) ON HIPERCHOLESTEROLEMIA: LITERATURE REVIEW - Nadila Ayuni Putri; Mira Sri Gumilar (Poltekkes Kemenkes Jambi, 2019)
Background: Indonesia has health problems nowadays in the form of both communicable and non-communicable diseases (PTM). One risk factor for PTM is high cholesterol levels in the blood (hypercholesterolemia). Increased cholesterol levels can cause health problems such as gallstones, hypertension, strokes to heart attacks. In Indonesia, based on Basic Health Research (Riskesdas) data, the prevalence of hypercholesterolemia at the age of 15 years in 2013 was 35.9% and the prevalence in 2018 decreased by 28.8%. Although based on the Riskesdas hypercholesterolemia data has decreased, but this figure is still above the prevalence of hypercholesterolemia in Southeast Asia in 2013 and is slightly below the prevalence of southeast Asia in 2018 so based on these data, hypercholesterolemia is one of the health problems in Indonesia. Content: Hypercholesterol can be reduced by using drugs such as statins and fibrates. In long-term use, these drugs have various side effects. As an alternative use foods that contain bioactive components that are useful for controlling cholesterol levels. One of them is avocado. Avocados are highly recommended by AHA in lifestyle guidelines to reduce the risk of cardiovascular disease. This fruit is also called cholesterol-free fruit because it contains MUFA. Not only the fruit, based on several studies in mice, has even proven that avocado leaf extract and its seeds have an antihyperlipidemic effect. In addition to providing the benefits of avocados also has disadvantages, but when compared to the benefits, the benefits of avocados are far greater than the disadvantages. Conclusion: Consumption of avocados (Persea americana) can reduce LDL and triglyceride levels, thereby reducing hypercholesterolemia.